Management Information Systems - A. Brien James (Mc Graw Hill Irwin, 2008)
This is a benchmark text for the syllabus organized by technology (a week on databases, a week on networks, a week on systems development, etc.) taught from a managerial perspective. O'Brien defines technology and then explains how companies use the technology to improve performance. Real world cases finalize the explanation.